2016
DOI: 10.1159/000440951
|View full text |Cite
|
Sign up to set email alerts
|

Paraxial <b><i>Nodal</i></b> Expression Reveals a Novel Conserved Structure of the Left-Right Organizer in Four Mammalian Species

Abstract: Nodal activity in the left lateral plate mesoderm is a conserved sign of irreversible left-right asymmetry at early somite stages of the vertebrate embryo. An earlier, paraxial nodal domain accompanies the emergence and initial extension of the notochord and is either left-sided, as in the chick and pig, or symmetrical, as in the mouse and rabbit; intriguingly, this interspecific dichotomy is mirrored by divergent morphological features of the posterior notochord (also known as the left-right organizer), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
(73 reference statements)
1
19
1
1
Order By: Relevance
“…g 50 µm. primitive streak, this mesenchymal axial mesoderm will be addressed here as SCM in accordance with observations made in the chick [Tsikolia et al, 2012] and several non-primate mammals [Schröder et al, 2016]. The SCM itself is covered -similar to the primitive streak mesoderm further posteriorly -by a single layer of squamous hypoblast cells (Fig.…”
Section: Morphology Of Human Embryossupporting
confidence: 58%
See 3 more Smart Citations
“…g 50 µm. primitive streak, this mesenchymal axial mesoderm will be addressed here as SCM in accordance with observations made in the chick [Tsikolia et al, 2012] and several non-primate mammals [Schröder et al, 2016]. The SCM itself is covered -similar to the primitive streak mesoderm further posteriorly -by a single layer of squamous hypoblast cells (Fig.…”
Section: Morphology Of Human Embryossupporting
confidence: 58%
“…42502-04-12/0708) [Aeckerle et al, 2015]. Parts of the embryos not required for this purpose were used for this study and subjected to different embedding protocols after dissection: embryo GM79.01 (recovered at 46 dpc and classified as stage 8b) was dehydrated in a graded series of ethanol and stored in ethanol at -20 ° C until its later use for whole-mount in situ hybridization (WISH, see below), after which Technovit ® 8100 (Heraeus Kulzer GmbH, Wehrheim, Germany) served as embedding medium for high-resolution histology and cellular localization of nodal mRNA expression as described previously [Schröder et al, 2016]. Sections (5 µm) were transferred in pairs onto glass slides and a few glass slides were used for test staining (their WISH staining reaction remaining accidentally unphotographed) to identify the staining technique which would enable easy identification of cellular borders and thus detailed 3-dimensional reconstruction (3DR) afterwards (s.b.).…”
Section: Jacchus Embryosmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, cell-tracking experiments revealed that asymmetric cell movements around Hensen's node set up asymmetric signalling in the chicken embryo [81]. Intriguingly, the node in the pig embryo also lacks cilia [81] and, unlike the mouse ventral node that is exposed to extraembryonic fluid, pig node cells are covered by a layer of cells referred to as subchordal mesoderm [82]. The node of the cow embryo is also enclosed in subchordal mesoderm [82], suggesting multiple vertebrates use ciliaindependent mechanisms to establish LR asymmetry.…”
Section: (C) Laterality Cues For Cilia?mentioning
confidence: 99%